Mænd, Migration og Byrum i Grænselandet mellem Spanien og Marokko - Sørensen, Ninna Nyberg (Kvinder, Køn & Forskning, 2000)
The article analyses the narratives of three male bordercrossers from Tetuán, a northern Moroccan city. Together with the overall majority of Tetuani inhabitants, these men share a critical view on Spain and Spaniards, simultaneously as their symbolic resistance towards the Moroccan state and the former King Hassan II is expressed by making reference to Spanish ethno- and landscaping.